A Regional Landslide Stability Analysis Method under the Combined Impact of Rainfall and Vegetation Roots in South China - Qinghua Gong; Jun Wang; Ping Zhou; Min Guo (Advances in Civil Engineering)
The aim of this study was to develop a regional landslide stability analysis method considering the combined impact of rainfall and the roots of vegetation in densely vegetated areas. A typical mountainous watershed in the Nanling National Nature Reserve of South China was chosen as the study area. First, the unmanned aerial vehicle (UAV) method was used to obtain surface element information including topography, vegetation, and landslides. Five main plant species were identified. The RipRoot model was then used to calculate the additional cohesion of these five plant species, and the relationship between the root systems of the different plant species and the soil shear strength was subsequently revealed. Finally, the root cohesion was introduced into the stability index mapping model (SINMAP), and the receiver operating characteristic curve (ROC) method was used to calculate the accuracy of slope stability when considering only soil cohesion as well as the composite cohesion of both soil and roots. The results showed significant differences in the root cohesion of different plants in the study area and a significant increase in the calculation accuracy (from 90% to 95.6%) when root cohesion was considered in the landslide stability calculation. These study results not only enrich theoretical studies on the impact of vegetation roots on landslide stability but also provide a scientific support for preventing disasters in mountainous landslide-prone areas.